Indigenous Identity in the Global Sustainable Project: The implementation of REDD+ in Cardamom Cambodia and Hieu Vietnam - Mahendra, Yusril Ihza; Kurniawan, Eduardus Andhika; Segara, Balya Arung (Nation State: Journal of International Studies, 2024)
REDD+ is an international initiative focused on mitigating the adverse effects of climate change. Developing countries can secure funding from developed countries to preserve their forests. However, despite the ideal goals set, the project's achievements varied due to differences in responses among local communities in several areas. This research employs anthropological perspectives and ecological knowledge of worldviews to analyse the factors that contribute to these discrepancies. By analysing REDD+ in Cardamom and Hieu Commune, it was discovered that there are variations in how indigenous people perceive their relationship with the environment. In this case, the Cardamom community perceives the environment as a source that will provide all their essential needs. Meanwhile, in Hieu Commune, people follow traditional methods to manage the natural woodlands, embracing the concept of a sacred forest, where taboos, spiritual beliefs, or religious convictions protect nature. These distinctions subsequently lead to variations in locals’ responses to REDD+, which in turn can impact the success of project implementation.